2001
DOI: 10.1177/03635465010290060401
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Untreated Acute Grade III Acromioclavicular Separations

Abstract: We prospectively studied the natural history of untreated acute grade III acromioclavicular separations. Twenty-five patients were treated nonoperatively with a sling for comfort through progressive early range of motion as tolerated. Ten additional uninjured subjects underwent strength testing to evaluate the difference between the dominant and nondominant sides so that patient data could be standardized. The patients were examined at intervals of 6, 12, 24, 36, and 52 weeks after injury, at which time they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(72 citation statements)
references
References 21 publications
0
69
0
3
Order By: Relevance
“…35 Return to sports should be delayed until full, painless range of motion is obtained, which may require 3 months. Schlegel et al 78 showed favorable outcomes in 80% of their patients after nonoperative treatment at 1 year of follow-up, and others have found similar success with up to 5 years of follow-up. 26,92 Functional deficits are minimal, with the objective evaluation of shoulder strength reported to be similar to that of the contralateral shoulder at midterm follow-up.…”
Section: Treatment Type I and Type Ii Injuriesmentioning
confidence: 87%
“…35 Return to sports should be delayed until full, painless range of motion is obtained, which may require 3 months. Schlegel et al 78 showed favorable outcomes in 80% of their patients after nonoperative treatment at 1 year of follow-up, and others have found similar success with up to 5 years of follow-up. 26,92 Functional deficits are minimal, with the objective evaluation of shoulder strength reported to be similar to that of the contralateral shoulder at midterm follow-up.…”
Section: Treatment Type I and Type Ii Injuriesmentioning
confidence: 87%
“…Management of type III injuries remains controversial. While nonoperative treatment can be successful, studies have shown that residual functional deficits may persist, including scapulothoracic dyskinesis, which may require further therapeutic intervention [11,12].…”
Section: Complication From Nonoperative Management Of Acromioclaviculmentioning
confidence: 99%
“…Schlegel et al 16 prospectively investigated the natural history of type III AC separations when given a sling for up to 2 weeks, course of early ROM, and pain medication among 20 active subjects. The authors concluded that, at 1-year follow-up, 80% of the cases had a satisfactory result, 14 of 16 subjects did not experience pain related to the injury when engaging in strenuous physical activity, and only 3 subjects reported weakness with overhead activities and bench press activities if done in a repetitious fashion; 88% reported a residual deformity.…”
Section: Discussionmentioning
confidence: 99%